OMON MUXTOR IJODIDA LIRIK VA EPIK TASVIR UYG‘UNLIGI (“Ko‘zgu oldidagi odam” romani misolida) - Xo‘jamqulov, A.J. (SCIENCE and SOCIETY, 2022)
This article discusses the combination of lyrical and epic imagery in Omon Mukhtor's novel "The Man in the Mirror" one of the greatest figures in modern Uzbek literature.
Keywords: lyrical type; epic type; lyro-epic image; novel; plot; composition; epigraph; modern literature